2012
DOI: 10.1111/j.1365-2702.2012.04067.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of individuals with schizophrenia living in the community: relationship to socio‐demographic, clinical and psychosocial characteristics

Abstract: Health care providers should make use of community-oriented intervention programmes that aim to strengthen psychosocial functioning. Particularly, programmes that enhance health status and mutuality should be identified and developed for both individuals with schizophrenia and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 45 publications
8
34
2
2
Order By: Relevance
“…Regarding professional/employment status, the results are congruent with other studies where those who were employed/students obtained higher QLS 7 PT scores when compared to the non-active or disabled individuals. These conclusions corroborate those of other studies that focus on the importance of occupational activity in the quality of life of people with schizophrenia (10,(14)(15)(16) . In view of these facts, being active seeking work, as well as implementing protected jobs and raising awareness of employers about the importance of inserting people with this pathology into the workplace is crucial for rehabilitation of these patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding professional/employment status, the results are congruent with other studies where those who were employed/students obtained higher QLS 7 PT scores when compared to the non-active or disabled individuals. These conclusions corroborate those of other studies that focus on the importance of occupational activity in the quality of life of people with schizophrenia (10,(14)(15)(16) . In view of these facts, being active seeking work, as well as implementing protected jobs and raising awareness of employers about the importance of inserting people with this pathology into the workplace is crucial for rehabilitation of these patients.…”
Section: Discussionsupporting
confidence: 82%
“…A study that also used QLS found similar results that a longer duration of the disorder and an older age would be associated with a worse quality of life (21) . In this sense, another study showed that a longer duration of the disorder was a predictor for worse quality of life, despite age not being significantly related to quality of life (15) . Regarding medication, participants who received firstgeneration neuroleptics had worse results on the quality of life scale than those who were only receiving second-generation neuroleptics, indicating that this type of neuroleptic may negatively influence the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the marital status is also not showing any significant relation as they also found to be somewhat equal in numbers with more for the married individuals. It is opposite to the previous study which found marriage as an effective factor for early recovery and improved quality of life [18][19][20]. This might be due to the increased marital discords and disharmony between couples which itself now becoming an active factor for relapse this episode The stressful life events has an great impact on functional recovery of patients.…”
Section: Discussioncontrasting
confidence: 52%
“…In the past years, QOL has become an important outcome measure for those patients, although the associations between predictors and QOL are rather unclear. Several cross-sectional studies have investigated the relationship between the subjective QOL of people with severe mental disorders and socio-demographic and clinical characteristics (Norman et al, 2000;Fitzgerald et al, 2001;Becchi et al, 2004;Caron et al, 2005aCaron et al, , 2005bHofer et al, 2006;Narvaez et al, 2008;Hsiao et al, 2012;Fujimaki et al, 2012). In addition, some studies have explored the mediating role of self-related factors, such as lower self-esteem, lack of perceived social support and low self-efficacy in QOL appraisal (Bechdolf et al, 2003;Ritsner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%